Investigating the Impact of Growth Temperatures on the ZnO Nanorods Properties Grown with Simplest Spray Technique - Jaqsi, Mohammed Kadhim; Kareem, Awaz; Abdulrahman, Ahmed (Science Journal of University of Zakho, 2023)
The simplest chemical spray approach has been used to grow the zinc oxide (ZnO) nanorods (NRs). For spraying, a basic perfume automizer was employed. Additionally, utilizing a variety of characterization techniques, the effects of various growth temperatures on the ZnO NRs properties were looked into and evaluated. The results of the investigation demonstrated that the growing temperature significantly affects all-characteristics properties of the ZnO NRs fabricated using the most straightforward spray approach. At various growth temperatures, the average diameters (size) and average crystalline sizes along with (002) of grown ZnO NRs were in the ranges of (47.89-51.29) nm and (44.128-52.565) nm, respectively. The hexagonal wurtzite plane was the optimum direction for ZnO NRs to be oriented, and as growth temperatures are raised. The absorption edge changed toward longer wavelengths and as growth temperature increased, the average absorbance also increased. The optical analysis reveals that the direct Eg. of the produced ZnO NRs lies in the (3.182-3.250) eV range.